PSYCHOLOGICAL EFFECTS OF COLOR AND COLOR THERAPY: रंगो का मनोवैज्ञानिक प्रभाव एवं रंग चिकित्सा - Chaudhary, Abhilasha (International Journal of Research -GRANTHAALAYAH, 2014)
And the mind has a close relationship, we all know this. A healthy mind selects a healthy body and a healthy body. Color is the medicine of mind and soul and hence it has the ability to resist various physical mental diseases. Colors have an important place in the life of a human being. Varna is an element entirely dependent on light and vision. The absence of even one proves to be a hindrance to the knowledge of color. Every object must have some color and basically the objects are identified due to their surface color and the amount of light is more or less the same color makes the object appear different. और मन का घनिश्ठ सम्बन्ध है, ये तो हम सभी जानते है। स्वस्थ मन स्वथ्य षरीर शरीर और स्वस्थ्य षरीर ही निर्विकार मन का वरण करता है। रंग, मन और आत्मा की औशधि है और इसीलिये वह विभिन्न षारीरिक मानसिक रोगों का प्रतिरोध करने की क्षमता रखती है। मनुष्य के जीवन में रंगों का महत्वपूर्ण स्थान है। वर्ण पूर्णतः प्रकाष व दृश्टि पर निर्भर तत्व है। एक की भी अनुपस्थिति रंग के ज्ञान में बाधक सिद्ध होती है। प्रत्येक वस्तु का कोई न कोई रंग अवष्य होता है और मूलतः वस्तुओं की पहचान उनके धरातलीय रंग के कारण ही होती है तथा प्रकाष की मात्रा के कम या अधिक होने से एक ही रंग की वस्तु अलग-अलग दिखलायी पडती है।